2021
DOI: 10.12998/wjcc.v9.i34.10595
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam benzenesulfonate anesthesia effectiveness in cardiac surgery patients under general anesthesia

Abstract: BACKGROUND Sedation with propofol injections is associated with a risk of addiction, but remimazolam benzenesulfonate is a comparable anesthetic with a short elimination half-life and independence from cell P450 enzyme metabolism. Compared to remimazolam, remimazolam benzenesulfonate has a faster effect, is more quickly metabolized, produces inactive metabolites and has weak drug interactions. Thus, remimazolam benzenesulfonate has good effectiveness and safety for diagnostic and operational sedat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…Remimazolam decreased the incidence of hypotension and low SpO 2 . 49 , 52 The safety data of ASA class III patients were in line with the corresponding data from patients with ASA class I and II. 50 Remimazolam could reduce the incidence of postoperative nausea and vomiting in the patients after laparoscopic gynaecological surgery under general anaesthesia as compared with desflurane (27% vs 60%, P=0.02) during the early postoperative period.…”
Section: Clinical Usessupporting
confidence: 69%
See 1 more Smart Citation
“…Remimazolam decreased the incidence of hypotension and low SpO 2 . 49 , 52 The safety data of ASA class III patients were in line with the corresponding data from patients with ASA class I and II. 50 Remimazolam could reduce the incidence of postoperative nausea and vomiting in the patients after laparoscopic gynaecological surgery under general anaesthesia as compared with desflurane (27% vs 60%, P=0.02) during the early postoperative period.…”
Section: Clinical Usessupporting
confidence: 69%
“…51 Moreover, remimazolam was proven effective for use in general anaesthesia among patients undergoing cardiac surgery by reducing hemodynamic fluctuations; moreover, the amount of norepinephrine was significantly lower, as compared with that in the propofol group. 52,53 It was concluded that remimazolam can safely avoid the risk of cardiac suppression when used in general anaesthesia among patients with severe aortic stenosis. 54 RT was first compared with propofol for use in general anaesthesia among patients with liver cirrhosis (ASA class II or III) undergoing endoscopic variceal ligation (EVL) (ChiCTR2100045710).…”
Section: Induction and Maintenance Of General Anaesthesiamentioning
confidence: 99%
“…Although Tang’s study is different from the operation type, inflammatory index and time point of this study, it still deserves good reference. Their study also claimed that compared with propofol, remimazolam benefited cardiac surgery patients under general anesthesia by reducing hemodynamic fluctuations [ 19 ]. Our study showed that there were statistical differences in the heart rate, MAP, plasma epinephrine, norepinephrine and cortisol in the two groups from the aspect of interaction effect, and the heart rate and MAP at T 1 , T 2 and T 3 in the two groups were significantly decreased compared with those at T 0 , and the levels of plasma epinephrine, norepinephrine and cortisol in the two groups were significantly increased at 24 h and 72 h after surgery compared with those before anesthesia induction but the levels were significantly lower in the remimazolam group than those in the propofol group, and the heart rate and MAP at T 1 , T 2 and T 3 in the remimazolam group were significantly higher than those in the propofol group, indicating that the influence of remimazolam on circulation is smaller than that of propofol during induction and remimazolam can maintain a more stable heart rate and MAP after induction and is more conducive to relieving the stress response of elderly patients during anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…As an esterbased medication, it is hydrolyzed quickly with a more rapid offset than midazolam and a limited context-sensitive half-life. Initial clinical experience in adults has demonstrated its efficacy for procedural sedation as well as an acceptable safety profile that includes limited effects on hemodynamic function, lack of pain with intravenous administration, organ-independent metabolic clearance, a reduced incidence of PONV, and a rapid return to baseline neurologic function [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%